Surface Modification With Gelatin For Polyurethane Vascular Grafts: A Review - Adipurnama, Iman; Yang, Ming Chien; Ciach, Tomasz; Raszeja, Beata Butruk (Jurnal Bahan Alam Terbarukan, 2019)
The means for developing synthetic vascular grafts to replace blood vessels is increasing extensively because of the limited supply of autologous vessels. Synthetic polymers as the alternatives still suffer from restenosis and thrombus formation. Natural polymers, on the other hand, are commonly biocompatible and biodegradable, compliment the synthetic ones. Blending, grafting and coating of natural polymers have been proposed to improve surface properties of synthetic polymers. Gelatin is a promising candidate to help improving synthetic vascular grafts surface owing to its ability to promote cell adhesion without promoting platelet aggregation at its surface. In this review, several techniques to incorporate gelatin onto synthetic polymers, mainly polyurethane, for vascular grafts application are summarized, together with the recent updates and potential development in the future.